2017
DOI: 10.20524/aog.2017.0205
|View full text |Cite
|
Sign up to set email alerts
|

Parenchyma-sparing hepatectomy (PSH) versus non-PSH for bilobar liver metastases of colorectal cancer

Abstract: Background:Preoperative interventions have increased the resectability of colorectal cancer (CRC) liver metastases. This retrospective study compares outcomes after liver resection for bilobar CRC metastases between patients who underwent parenchyma-sparing hepatectomy (PSH), i.e., segmentectomies and smaller resections on both lobes, and those treated with non-PSH, i.e., hemihepatectomy plus any resection on the other lobe.Methods:A cohort of 119 patients who underwent liver resection for bilobar CRC metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Multivariate analysis for predictors of postoperative morbidity in the entire study cohort confirmed that PSR was significantly associated with less postoperative complications, independently of the tumor burden. These results are in concordance with previous studies confirming that PSR is a feasible and safe technique [35,36] not only for patients with solitary lesions [21] but also for patients with multiple [17], bilobar [22], and deep-placed [23] CRLM. Postoperative liver failure which remains the main cause for posthepatectomy mortality [37] occurred equally frequently after PSR and non-PSR in our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Multivariate analysis for predictors of postoperative morbidity in the entire study cohort confirmed that PSR was significantly associated with less postoperative complications, independently of the tumor burden. These results are in concordance with previous studies confirming that PSR is a feasible and safe technique [35,36] not only for patients with solitary lesions [21] but also for patients with multiple [17], bilobar [22], and deep-placed [23] CRLM. Postoperative liver failure which remains the main cause for posthepatectomy mortality [37] occurred equally frequently after PSR and non-PSR in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The oncological radicalness (R0) of PSR in our practice was similarly adequate as non-PSR both in patients with lower tumor burden (p = 0.604) and patients with extended disease (p = 0.892). Several studies have reported on equal R0 resection margin rates between PSR and non-PSR both for open liver surgery [20][21][22] and minimal-invasive hepatectomy [17]. Routine intraoperative ultrasound monitoring during liver parenchyma transection to identify the exact proximity of liver lesions to neighboring vascular structures and define the resection limits [32] as well the use of advanced energy devices and high-definition optics in laparoscopic surgery [19] have contributed to these results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lordan and colleagues performed a case-control study of 238 parenchyma-sparing hepatectomies with 238 major hepatectomies and showed less need for perioperative blood transfusions, lower rate of postoperative complications, and improved 90-day mortality in a group of parenchyma-sparing hepatectomies. 23 Most recent comparative study in regard to parenchyma-sparing liver resections for colorectal metastases published by Spelt et al 25 has concluded about benefits of parenchyma-sparing techniques in a form of shortened operative time and hospital stay and less intraoperative blood loss, whereas other perioperative variables, including oncologic outcomes, were similar. However, that study had several shortcomings.…”
Section: Discussionmentioning
confidence: 99%